Diseño de un sistema administrtaivo, contable y tributario para la empresa Humboldt Management - Martínez Ruiz, Paola Carolina (2011)
The systems were developed in order to count Humboldt Management with a base that allows it to grow to its administrative structure is right and take their resources for decision-making. This thesis project is based on a detailed study of the processes administrative, accounting and tax systems organized as follows: In Chapter I, the theoretical framework is developed where, the conceptual bases arise legal and serving as support in the development of different systems. In Chapter II a situational analysis of the company is from your review historical and services presents an analysis of its strengths, weaknesses and threats. Chapter III presents an approach based on phases of planning administrative system, organization, management and control to adapt to the strategic objectives of the company. When planning what we want to do and what it will do to achieve this, the We see how it will organize to plan. In the address stage establish guidelines for planned is made and finally at the stage of Control will review and have been made the previous phases.